La imagen en primer plano: La pasión de Juana de Arco y el poder del rostro - Alayza Prager, Cristina (2016)
Two peculiarities of the film The Passion of Joan of Arc (Carl Theodor Dreyer,1928) are explored in this essay: its unusual close-ups and its strongly expressivecharacter. We start from the idea that both characteristics are closely related andwe seek to clarify this relationship making use of Gilles Deleuze’s affection-image and Georges Didi-Huberman’s dialectical image.